The Role of the Principal’s Visionary Leadership in Enhancing the Quality of Public Elementary School - Herlinda, Herlinda; Harjito, Harjito; Nurkolis, Nurkolis (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2026)
This study aims to analyze the influence of the principal’s visionary leadership in improving the quality of education at SD Negeri Jrebengkembang, Karangdadap District, Pekalongan Regency. The research employed a qualitative descriptive approach with a case study design, enabling the researcher to gain an in-depth understanding of visionary leadership practices within the real context of an elementary school. The study focused on four main dimensions of visionary leadership: the principal as a formulator of vision, a driver of change and innovation, an effective communicator, and a mentor who fosters teachers’ professionalism. Data were collected through direct observation of leadership activities at school, in-depth interviews with the principal, teachers, students, and the school committee, as well as document analysis covering the school’s vision and mission statements, work plans, and supervision reports. Data analysis followed the interactive model of Miles, Huberman, and Saldana (2014), which consists of data reduction, data display, and conclusion drawing and verification. The findings indicate that the principal implemented a coaching-based leadership approach emphasizing teacher empowerment, professional reflection, collaboration with the community, and the reinforcement of a religious and character-driven school culture. This approach effectively enhanced both teacher and student motivation, improved the learning climate, and fostered a shared sense of ownership toward the school’s vision. The study concludes that the integration of visionary leadership and coaching practices can transform schools into adaptive, innovative, and sustainable learning communities, while contributing both theoretically and practically to the advancement of educational management quality in Indonesia.